2019
DOI: 10.3390/ma12040647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Molding Method and Blank Size of Green Body on the Sintering Densification of Magnesia

Abstract: The bulk density of sintered magnesia is significantly influenced by molding methodology and blank size of the green body during dry pressing. The entrapped air in the green body plays a critical role in determining the bulk density of magnesia samples. Herein, high-density magnesia samples, with different sizes, are prepared by using vacuum compaction molding and conventional compaction molding. The physical properties, such as bulk density and pore size distribution, and morphology or as-sintered magnesia sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The properties of the sintered MgO, especially the bulk density and grain size, are important factors limiting the service life and service range of MgO refractories. In order to obtain MgO refractories with excellent properties, the bulk density of the sintered MgO is required to be more than 3.40 g•cm -3 with a grain size over 40 µm [2]. In the traditional process, the bulk density of the sintered MgO is generally enhanced by increasing the sintering temperature (more than 1800 °C) or the moulding pressure of the green body [3].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the sintered MgO, especially the bulk density and grain size, are important factors limiting the service life and service range of MgO refractories. In order to obtain MgO refractories with excellent properties, the bulk density of the sintered MgO is required to be more than 3.40 g•cm -3 with a grain size over 40 µm [2]. In the traditional process, the bulk density of the sintered MgO is generally enhanced by increasing the sintering temperature (more than 1800 °C) or the moulding pressure of the green body [3].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue, “High Temperature Ceramic Materials”, released by Materials, is dedicated to original research articles from the ceramics/refractories communities, presenting some of the latest work in a few topical areas listed above. In total, 15 good quality articles have been included [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], the interesting points from each of which are briefly highlighted as follows.…”
mentioning
confidence: 99%
“…Given the importance of shape-forming and subsequent sintering/densification in the preparation of bulk ceramics, Jin et al [ 10 ] have investigated and compared sintering/densification behaviours of MgO green samples resulting, respectively, from a conventional air compaction and a novel vacuum compaction. They have found that air pockets entrapped in the green samples play an important role in their densification and defect formation.…”
mentioning
confidence: 99%